Factors That Influence The Interest of Women of First Age Couples to do Pap Smear at Poskesdes Suka Makmur, Subulussalam City In 2020 - Yulida Effendy Nasution; Wardiah; Siti Hawa (International Archives of Medical Sciences and Public Health, 2021)
The Indonesian Ministry of Health targets 50% cancer early detection coverage program for women aged 30-50 years to be achieved in 2019. Until 2014, the coverage for early detection of cervical cancer that has been carried out is still low, namely 2.45% with positive pap smear results. 4.94% and cervical cancer suspects as many as 1,056 people. In Indonesia, cervical cancer is the number one killer of all cancers. The aim of the study was to determine the factors that influence the interest of women with PUS to do Pap smear at the Suka Makmur Poskesdes Kota Subulussalam in 2020The design of this study was a quantitative analytic survey using a cross sectional study. The total population was 210 respondents and the sample used Accidental Sampling as many as 42 respondents. The data used were primary and secondary data. Data analysis using univariate and bivariate.The results of the study were obtained by using the chi square test, there was an effect of knowledge p = 0.011, there was an effect of information sources p = 0.004, there was an effect of distance to health facilities p = 0.034 on the interest of women with PUS to do papsmear at Poskesdes Suka Makmur, Subulussalam City in 2020.The conclusion is there is the influence of knowledge, information sources and distance to health facilities on the interest of women with PUS to do Pap smear at the Suka Makmur Poskesdes Kota Subulussalam in 2020. It is hoped that health workers will provide information on WPUS so that it can increase awareness of women in fertile age in conducting pap smear examinations.